Buying Behavior and Promotion in Textile Retailing in Kerala - Koshy, Moli P.; Suresh, N. (Indian Journal of Marketing, 2007)
Retail outlets are the main source of purchase for consumers. Around 80 percent of the customers buy goods from retailers, while 20 percent goes to the wholesalers and manufacturers. Textile retailing in Kerala used to be a business that earned huge profits with less investment. But today the situation has changed. To earn a meager profit huge investment is needed. Earlier the customers were not bothered about the ambience of the shop and display of goods, but now the urban customer considers these facts and the retailers are forced to give importance to these, and huge investments are needed for this. Also, the preferences of customers are changing rapidly. Thus retailing has become a difficult task, as they have to keep changing their product lines and modify products according to the changing trends.Nowadays retail business is not an easy job. The shops are trying hard for surviving, and sustain the same turnover every year. The main problems the retailers face today are financial crisis, lack of investment, less margin and competition. This is a vicious circle. Due to financial crisis the retailers are not able to invest more into their business as the customers are going for cheaper goods. And cheap products are available in plenty. So margins are very low due to stiff competition. Earlier, customers used to give high importance to the quality of their products. But now customers are very price conscious and are willing to pay only less for more. So the new generation retailers stock more of low quality goods to give goods at low prices. But still there are some people who go for quality goods.